1984
DOI: 10.1037/0022-3514.46.4.735
|View full text |Cite
|
Sign up to set email alerts
|

Gender stereotypes stem from the distribution of women and men into social roles.

Abstract: According to stereotypic beliefs about the sexes, women are more communal (selfless and concerned with others) and less agentic (self-assertive and motivated to master) than men. These beliefs were hypothesized to stem from perceivers' observations of women and men in differing social roles: (a) Women are more likely than men to hold positions of lower status and authority, and (b) women are more likely than men to be homemakers and are less likely to be employed in the paid work force. Experiments 1 and 2 fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

64
1,100
10
39

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,481 publications
(1,247 citation statements)
references
References 49 publications
64
1,100
10
39
Order By: Relevance
“…Prior research on gender stereotypes suggests that women are more able to devote themselves to others more generally (e.g., Conway et al, 1996;Deaux & Lewis, 1984;Eagly & Steffen, 1984). Women also self-report greater importance of universalism values than men, which suggests they extend concern to others beyond close relationships (Schwartz & Rubel, 2005).…”
Section: The Sociocultural Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Prior research on gender stereotypes suggests that women are more able to devote themselves to others more generally (e.g., Conway et al, 1996;Deaux & Lewis, 1984;Eagly & Steffen, 1984). Women also self-report greater importance of universalism values than men, which suggests they extend concern to others beyond close relationships (Schwartz & Rubel, 2005).…”
Section: The Sociocultural Perspectivementioning
confidence: 99%
“…Men and women may conform to these gender stereotypes to avoid being negatively evaluated by others (Costrich, Feinstein, Kidder, Marecek, & Pascale, 1975). Because women are perceived to be more cooperative than men (e.g., Eagly & Steffen, 1984), this stereotype may especially influence women to be more coopera-tive than men while interacting with an opposite-sex partner, compared to a same-sex partner (Deaux & Major, 1987). Thus, women are expected to be even more cooperative than men in mixed-sex (vs. same-sex) groups.…”
Section: Same-sex Versus Mixed-sex Interactionsmentioning
confidence: 99%
“…Locksley and her colleagues have argued that category-based expectancies have relatively little durability in the face of more individuating information (Locksley, Borgida, Brekke, & Hepburn, 1980;Locksley, Hepburn, & Ortiz, 1982). Similarly, Eagly and her colleagues have found that information about occupational roles outweighs gender as a basis of trait inference under certain conditions (Eagly, 1983;Eagly & Steffen, 1984;Eagly & Wood, 1982). Yet the influence of stereotypic categories may not be quite so ephemeral.…”
Section: The Perceiver Interprets the Target's Actionmentioning
confidence: 99%
“…Sin entrar aquí en la cuestión de si estas diferencias existen realmente o no, lo cual sería objeto de la psicología diferencial, lo que la psicología social ha demostrado es que la gente cree que existen y utiliza dicotomías muy similares a la de Simmel para describir a hombres y mujeres. Las primeras investigaciones en las que se analizó el contenido de los estereotipos de género (Broverman, Vogel, Broverman, Clarkson y Rosenkrantz, 1972;Rosenkrantz, Vogel, Bee, Broverman y Broverman, 1968) establecieron una distinción entre los rasgos relacionados con la competencia y los asociados a la expresividad emocional, dicotomía que es conceptualmente similar a la que estudios posteriores utilizaron para distinguir entre instrumentalidad y expresividad (Spence, Helmrecih y Stapp, 1975), o entre agencia y comunalidad (Deaux y Lewis, 1984;Eagly y Steffen, 1984;Williams y Best, 1982). En todas estas dicotomías los hombres se perciben como competentes, asertivos, independientes y orientados hacia el poder y el logro, mientras que las mujeres se perciben como afectivas, dependientes, sociables, poco preocupadas por ellas mismas y orientadas hacia los demás.…”
Section: Estereotipos De Género Y División Del Trabajounclassified
“…Son estas diferencias en los roles sociales y laborales que desempeñan hombres y mujeres 5 de 14 doi: https://doi.org/10. 16925/pe.v14i23.2261 las que dan lugar a la formación y el mantenimiento de los estereotipos de género (Eagly y Steffen, 1984). En este sentido, es previsible que el cambio que se ha producido en los roles laborales de las mujeres haya tenido algún efecto en el contenido de los estereotipos.…”
Section: Estereotipos De Género Y División Del Trabajounclassified